(untitled) (Education in the 21st Century, 2023)
Human resource management in higher educational institutions is a process in which "the heads of the structure provide the necessary number of employees who are able to solve the intended tasks effectively, have the appropriate qualifications and skills to achieve the strategic goals of the institution" / Khachatryan R. et al., p. 55/. The human potential of any university is the main source of its competitive advantage, which the result of the activity of the structure and its rating depends on. While without effective human resource management, it is impossible to implement far-reaching plans and long-term goals. From this point of view, the article presented the experience of higher education management in different countries, the best sides, achievements and differences.